Knowledge and behavior treatment pattern related to dengue among community in kubang kerian, Kelantan - Husain, Nur Fatini (Universiti Sains Malaysia, 2016)
Dengue fever had causes significant morbidity and mortality; and is endemic in Malaysia. A gradual upsurge was seen in the number of dengue cases in the last decade since the disease was made notifiable in the country. Till date, there is no vaccine and the manner to prevent and control dengue is by preventing transmission of disease. The objective of this study was to determine the knowledge and behavior treatment pattern related to dengue among community in Kubang Kerian, Kelantan. A cross sectional study of 175 respondents living in Bandar Baru Kubang Kerian, Kelantan was conducted using a self-administered survey questionnaire sampled by simple random selection. The finding shows that communities had moderate knowledge level (52.8%) and poor level of behavior treatment pattern related to dengue fever (69.7%). Results revealed a significant association between knowledge and behavior treatment pattern related to dengue among community (p<0.05), knowledge on sign and symptoms of dengue with level of education (p=0.001), monthly income (p=0.004) and dengue experience (/?=0.001). However, there is no association to all selected sociodemographic characteristic with behavior treatment pattern related to dengue (p>0.05). It can be concluded that knowledge about dengue is inadequate. Therefore, concerted effort by healthcare professionals and the Ministry of Health Malaysia authorities is needed to educate communities to identify the sign and symptoms of dengue and to improve their health seeking behavior for prompt public health intervention